Морфолошки карактеристики и клиничко значење на вертебробазиларниот систем - Додевски, Аце (Медицински факултет, УКИМ, Скопје, 2015)
In modern clinical diagnostics the vertebrobasilar system is being examined with diverse techniques and procedures such as: angiography, ultrasound, Doppler ultrasound, magnetic resonance imaging and computed tomography. A wide range of procedures in diagnostic and interventional radiology and surgery require detailed knowledge of the anatomy of the vertebrobasilar system, especially of the anatomical variations. Aim of the study: The aim of this study was to investigate the morphological characteristics and anatomical variations of the vertebrobasilar system in terms of: origin of the vertebral artery, the level of entry into the transverse foramen of the vertebra, the degree of twist, the release of lateral branches and their diameter, shape and diameter of basilar artery and the side branches and their diameter. Material and Methods: The study included a sample of 158 patients of both sexes over 18 years old. Subjects were divided into two groups. The first group of 103 subjects was examined by computed tomography angiography. The second group of 55 subjects was examined by digital subtraction angiography by Seldinger method. Results: In the study conducted by computed tomography angiography the left vertebral artery originated from left subclavian artery in 94.17% of the patients. The left vertebral artery emerged from the aortic arch in 5.82%. The right vertebral artery originated from the right subclavian artery in 99.02% of the patients. In 0.97% the right vertebral artery arose from the right common carotid artery. The mean diameter of the left vertebral artery was 3.33 ± 0.76 mm, and the mean diameter of the right vertebral artery was 3.20 mm ± 0.74 mm. Hypoplasia of the vertebral artery was observed in 11.64% of the patients. Hypoplasia of the right and of the left vertebral artery was observed in 6.79% and 4.85% of the patients, respectively. The left vertebral artery entered the transverse foramen at the level of sixth cervical vertebra in 92.23% of the patients, while the right vertebral artery entered at the same level in 94.17% of patients. The diameter of the left PICA was 1.24 mm, while the diameter of the right PICA was 1.18 mm. The average length of the basilar artery was 3.16 cm, while the average diameter of the basilar artery was 3.27 mm. The diameter of the left AICA, SCA and PCA was 0.89 mm, 1.36 mm and 1.94 mm, respectively. The diameter of the right AICA, SCA and PCA was 0.88 mm, 1.32 mm and 1.83 mm, respectively. Fenestration was registered in 3.89% of the patients. In a study conducted by the digital subtraction angiography the left vertebral artery had origin from the left subclavian artery in 96.36% of the patients. In 3.63% of the patients the left vertebral artery emerged as the fourth branch from the aortic arch. The right vertebral artery in all cases had origin from the right subclavian artery. In 90.9% of the patients SCA arose from the distal portion of the basilar artery on both sides as a single vessel. In 5.45% of the patients SCA arose as a duplicate trunk from the basilar artery. In 3.63% of the patients origin of the SCA from PCA was noticed as a single trunk from adult type of the PCA. The posterior cerebral artery had basilar origin in 74.54% of the patients on the left side and in 83.63% of the patients on the right side. Conclusion: Knowledge of morphological features and variations of the vertebrobasilar system is a basis for planning and accomplishing of diagnostic and interventional procedures in radiology and neurosurgery. The results obtained in this study can broaden the knowledge of the anatomists as well as they can serve as the most valuable teaching material for students and postgraduates.
Morphological characteristics of the vertebrobasilar system and its clinical significance
Докторска дисертација одбранета во 2015 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Добрила Тосовска Лазарова.
Keywords: vertebral artery, basilar artery, computed tomography angiography, digital subtraction angiography, anatomy, variations